The village food bank, against stunting on poor children in Sibalaya Barat - Lago, Rossalin (BKM Public Health and Community Medicine, 2021)
Sibalaya Barat Village is located in Tanambulava sub-district, Sigi Regency, Central Sulawesi. The prevalence of stunting of children under five in Tanambulava sub-district in 2019 was 21.6%, the third highest of 15 sub-districts. In 2020, the Sigi Regency Government has designated Sibalaya Barat village as one of the 10 locus for accelerating stunting reduction. Banua Ntovea is an innovation program to reduce stunting in Sibalaya Barat village.